Health System-Level Evaluation of Tele-Mental Health Services Among Children and Adolescents in Ontario, Canada. (June 2022) - Toulany, Alene; Kurdyak, Paul; Gandhi, Sima; Fu, Longdi; Grewal, Seena; Kulkarni, Chetana; Saunders, Natasha; Vigod, Simone; Guttmann, Astrid; Chiu, Maria; Pignatiello, Antonio
Objective: To describe the characteristics of children and adolescents receiving tele-mental health services in Ontario, Canada and examine access to a psychiatrist, in-person or via tele-mental health services, following a mental health and addictions (MHA)-related emergency department (ED) visit or hospitalization. Method: Using linked health and administrative data, we described two cohorts: (1) children and adolescents (1–18 years) who used a provincial tele-mental health programme from January 1, 2013 to March 31, 2017, comparing their MHA-related service use (outpatient, ED, hospitalization) in the 1 year prior to and the 1 year following initial consultation; (2) children and adolescents with high mental health service needs, defined as those with an incident MHA-related ED visit or hospitalization between January 1, 2013 and December 31, 2016, examining their 1-year follow-up with telemedicine and other health care utilization. Results: In the first cohort, 7, 216 children and adolescents (mean age 11.8 [±3.8] years) received tele-mental health services. The proportion of MHA-related ED visits [15.1% pre vs. 12.6% post (test statistic 23.57, P < 0.001)] or hospitalizations [10.2% pre vs. 8.7% post (test statistic 11.96, P < 0.001)] declined in the year following tele-mental health consultation, while local psychiatry visits increased [8.4% pre vs. 17.0% post (test statistic 298.69, P < 0.001)]. In the second cohort ( n = 84, 033), only 1.5% received tele-mental health services, 40.7% saw a psychiatrist in-person, and 32.5% received no MHA-related outpatient care in follow-up. Conclusions: Tele-mental health services were rarely used in Ontario, even among high-needs children and adolescents, despite their association with increased access to care and less need for acute mental health care.